Location of the Aerial Ambulances Using Combination of Fuzzy ANP and Fuzzy Dematel in the Environment of ArcGIS: A Case study in Sistan and Baluchestan province - Farzad Firouzi Jahantigh; mojtaba ghaderi (Tehran University of Medical Sciences, 2018)
Background: Among various emergency services, the air emergency due to access to the extreme areas, possibility to move more patients, providing higher quality treatment to the patient being carried and also access to the hospital without problems such as traffic and sudden crashes, is one of the most important types of emergencies in the health sector. So, the right location according to the scientific principles, enhances the efficiency of the aerial emergency. Materials and Methods: This descriptive- analytical present study was conducted as an applied research in Sistan and Baluchestan province in 2016. At first, indicators affecting the location of ambulances were identified. Then, the location using deploying a Fuzzy network analysis process model next to the Fuzzy Dematel technique and the integration with geographic information system was performed. Results: Criteria for selecting the best places for deploying air ambulances in Sistan and Baluchestan province are considered as proximity to the roads, appropriate tilt area, proximity to crowded areas, proximity to high risk passages, and the convenient distance from the medical emergencies. Output weights of the technique used for affecting on GIS software were calculated 0.244, 0.083, 0.435, 0.182 and 0.057, respectively. Conclusion: Study results revealed that number and coverage of aerial ambulances in cities and roads of Sistan and Baluchestan province are not suitable. Therefore, the map derived from the Fuzzy integration of the information layers identified by the effective factors, illustrated that the districts of Zabol and Iranshahr cities have the best status of selected criteria to establish the air emergencies bases in the province of Sistan and Baluchestan.